Palgrave Advances in John Clare Studies
XVII, 317 p. 4 illus.
Keywords: ‘This fine collection is an important contribution to Romanticism studies which will continue to be valued and read. Its essays are often fresh, original, and skillfully inserted into diverse contemporary critical conversations. The book reflects and advances recent developments in Clare scholarship in several areas: Clare’s strong community ties, the significant roles of sound and song in his verse, and, especially, his importance for modern ecocriticism.’ — Elizabeth Helsinger, University of Chicago, USA This collection gathers together an exciting new series of critical essays on the Romantic- and Victorian-period poet John Clare, which each take a rigorous approach to both persistent and emergent themes in his life and work. Designed to mark the 200th anniversary of the publication of Clare’s first volume of poetry, Poems Descriptive of Rural Life and Scenery, the scholarship collected here both affirms Clare’s importance as a major nineteenth-century poet and reveals how his verse continually provokes fresh areas of enquiry. Offering new archival, theoretical, and sometimes corrective insights into Clare’s world and work, the essays in this volume cover a multitude of topics, including Clare’s immersion in song and print culture, his formal ingenuity, his environmental and ecological imagination, his mental and physical health, and his experience of asylums. This book gives students a range of imaginative avenues into Clare’s work, and offers both new readers and experienced Clare scholars a vital set of contributions to ongoing critical debates.